Putting Religion Back Into Religious Ethics - Gregory, Eric (Journal of religious ethics, 2019)
This essay on Richard Miller's Friends and Other Strangers (2016) locates its arguments in the context of how the practice of religious ethics bears upon debates about normativity in the study of religion and the cultural turn in the humanities. After reviewing its main claims about identity and otherness, I focus on three areas. First, while commending Miller's effort to analogize virtuous empathy with Augustine's ethics of rightly ordered love, I raise questions about his use of Augustine and his distinctive formulation of Augustinian "iconic realism." Second, I suggest his discussion of public reason is at odds with the dialogical spirit of the book and may distract from the democratic solidarity required by our political moment. Third, more briefly, I highlight the practical implications of Miller's vision for higher education at both the graduate and undergraduate level.